HAVING EFFECTIVE TIME MANAGEMENT GIVE INFLUENCE STUDENTS’ ACADEMIC ACHIEVEMENT - Dalia, Arisa Cahyalaili; Putra, Fahry Rizaldy (Journal of Educational Learning and Innovation (ELIa), 2023)
This current study investigated having effective time management give influence students’ academic achievement. The aims of this study was explorehow to manage time effectively by providing explanations of theories related how to manage time effectively to provide good academic achievement for students. The research method used in this study was literature review. In this study, explore the importance of time management for students, how to manage time so that it can be effective, the benefits of time management effectively, what is academic achievement, and factors related to or supporting academic achievement. This study recommends that having an effective time management can be implemented for students improving academic achievement.